2016
DOI: 10.3892/ol.2016.5488
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of cholangiocarcinoma cell inhibition by medicinal plants

Abstract: Abstract. Cholangiocarcinoma (CCA) is one of the most common causes of cancer-associated mortality in Thailand. Certain phytochemicals have been demonstrated to modulate apoptotic signaling pathways, which may be targeted for the prevention and treatment of cancer. Therefore, the aim of the present study was to investigate the effect of specific medicinal plants on the inhibition of CCA cell proliferation, and to identify the molecular mechanisms underlying this. A WST-1 cell proliferation assay was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
1
12
0
1
Order By: Relevance
“…Furthermore, the extract was reported to have triggered apoptosis through the activation of phosphor-extracellular signal related kinase (p-ERK) and phosphor-c-Jun N-terminal kinase (pJNK) in human melanoma cancer cells (A2058) [ 69 ]. Similarly, an extract from M. oleifera seeds caused an increase in the phosphorylation level of ERK1/2 and p38 MAPK, which led to apoptosis in RMCCA1 [ 70 ]. The authors suggested that the activities of pro- and anti-apoptotic markers could be the benchmark for the apoptotic nature of the extract.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the extract was reported to have triggered apoptosis through the activation of phosphor-extracellular signal related kinase (p-ERK) and phosphor-c-Jun N-terminal kinase (pJNK) in human melanoma cancer cells (A2058) [ 69 ]. Similarly, an extract from M. oleifera seeds caused an increase in the phosphorylation level of ERK1/2 and p38 MAPK, which led to apoptosis in RMCCA1 [ 70 ]. The authors suggested that the activities of pro- and anti-apoptotic markers could be the benchmark for the apoptotic nature of the extract.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the administration of M. oleifera leaf extract resulted in a time-dependent increase of phosphor-c-Jun N-terminal kinase (p-JNK) and phosphor-extracellular signal-related kinase (p-ERK), without changes in total JNK or ERK protein, hinting at the possibility of a pro-apoptotic role of M. oleifera via activation of these kinases in human melanoma A2058 cells [ 61 ]. Interestingly, in cholangiocarcinoma (CCA), the phosphorylation levels of phospho-p44/42 MAPK (ERK1/2) and phospho-p38 MAPK increased in M. oleifera seed extract treated RMCCA1 cells, suggesting that the activity levels of anti- and pro-apoptotic signaling proteins may determine the apoptotic nature of this compound [ 62 ]. The extracts from M. oleifera leaves and bark also effectively arrest cell cycle progression at the G2/M phase and increase apoptosis in breast and colorectal cancer cell lines such as MDA-MB-231 and HCT-8 cells, which could be attributed to the bioactive compounds such as eugenol, isopropyl isothiocynate, D-allose, and hexadeconoic acid ethyl ester [ 52 ].…”
Section: Anticancer Property Of M Oleiferamentioning
confidence: 99%
“…Nesta revisão, foi possível avaliar que os compostos curcumina, epicatequina, lupeol, ácido cafeico, ácido ursólico e berberina se destacaram em virtude da sua atividade contra diversos tipos de câncer, especialmente em estudos in vitro, em que esses compostos foram isolados de plantas medicinais aplicadas em ensaios. A curcumina pode ser encontrada principalmente na Curcuma longa, e demostrou efeito sobre a diminuição da viabilidade celular do câncer de mama e de cólon, por promover acúmulo de espécies reativas de oxigênio (ERO), que pode promover estresse celular, fazendo com que a célula entre em processo de apoptose 32,81 .…”
Section: Discussionunclassified